2017
DOI: 10.1016/j.neuropharm.2017.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Studies using macaque monkeys to address excessive alcohol drinking and stress interactions

Abstract: The use of non-human primates (NHPs) in studies of volitional, oral self-administration of alcohol can help address the complex interplay between stress and excessive alcohol consumption. There are aspects to brain, endocrine and behavior of NHPs, particularly macaques, that provide a critical translational link towards understanding the risks and consequences of alcohol use disorders (AUDs) in humans. These include wide individual differences in escalating daily alcohol intake, accurate measures of hypothalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 104 publications
1
22
0
Order By: Relevance
“…The current study is the first study to our knowledge that has characterized the absorption and clearance rates of low‐to‐moderate EtOH doses and determined the GABA A and NMDA receptor involvement in moderate EtOH doses. These data fill an important gap in understanding the psychopharmacology of EtOH in the rhesus monkey, which is used in translational studies of alcohol drinking relevant to alcohol use disorders (Allen et al., ; Baker et al., ; Grant et al., ; Jimenez and Grant, ). The pharmacokinetic data indicate that the time to peak BEC following 1.0 g/kg (i.g.)…”
Section: Discussionmentioning
confidence: 94%
“…The current study is the first study to our knowledge that has characterized the absorption and clearance rates of low‐to‐moderate EtOH doses and determined the GABA A and NMDA receptor involvement in moderate EtOH doses. These data fill an important gap in understanding the psychopharmacology of EtOH in the rhesus monkey, which is used in translational studies of alcohol drinking relevant to alcohol use disorders (Allen et al., ; Baker et al., ; Grant et al., ; Jimenez and Grant, ). The pharmacokinetic data indicate that the time to peak BEC following 1.0 g/kg (i.g.)…”
Section: Discussionmentioning
confidence: 94%
“…Individual differences in stress and anxiety responses (Dilleen et al, 2012; Jimenez and Grant, 2017), social dominance (Morgan et al, 2002; Covington and Miczek, 2005), aggressive temperament (McClintick and Grant, 2016), preference for saccharine (Carroll et al, 2002), sensation or novelty seeking (Suto et al, 2001; Nadal et al, 2002; Belin et al, 2011; Flagel et al, 2014), impulsivity (Perry and Carroll, 2008; Verdejo-Garcia et al, 2008; Dalley et al, 2011), and sensitivity to rewards (Belcher et al, 2014) have all been found in both animal models and clinical studies in humans to be associated with addiction vulnerabilities, and in particular with the likelihood to develop and maintain addiction, or to resist to treatment (Piazza et al, 1989; Belin et al, 2016; Everitt and Robbins, 2016). However, investigations into the mechanisms underlying this phenotypic differentiation in addiction has so far revealed few neural or computational candidates, which are found associated with diverse and dissociable behavioral traits.…”
Section: Discussionmentioning
confidence: 99%
“…Although the transcriptome profiles were not an exact match between species, the constituent parts represented were remarkably consistent. Non-human primates are a valuable resource for conducting long-term studies on individual variation in alcohol drinking behavior (Jimenez & Grant, 2017). RNA-Seq of non-human primate brain tissue has highlighted the relationship between alcohol self-administration and dysregulation of synaptic signaling elements (Hitzemann et al, 2013).…”
Section: Integrative Analysis Of Human and Non-human Primate Brain Timentioning
confidence: 99%